Dead Cetacean? Beach, Bloat, Float, Sink - Moore, Michael J.; Mitchell, Glenn H.; Rowles, Teri K.; Early, Greg (Frontiers in Marine Science, 2020)
Variably buoyant, dead Cetacea may float, or sink and later bloat to refloat if ambient temperature and pressure allow sufficient decomposition gas formation and expansion. Mortality can result from acute or chronic disease, fishery entanglement, vessel collision, noxious noises, or toxicant spills. Investigators often face the daunting task of elucidating a complex series of events, in reverse order, from when and where an animal is found, to diagnose the cause of death. Various scenarios are possible: an animal could die at sea remaining there or floating ashore, or strand on a beach alive, where it dies and, if cast high enough, remain beached to be scavenged or decompose. An animal that rests low on a beach may refloat again, using increased buoyancy from decomposition gas and favorable tides, currents and wind. Here we review the factors responsible for the different outcomes, and how to recognize the provenance of a cetacean mortality found beached or floating at sea. In conclusion, only some carcasses strand, or remain floating. Negatively buoyant animals that die at depth, or on the surface, and sink, may never surface, even after decomposition gas accumulation, as in cold, deep waters gas may fail to adequately reduce the density of a carcass, precluding it from returning to the surface.